Pelatihan Penelitian Kualitatif melalui Web Seminar - Qadri, Resi Ariyasa; Firmansyah, Amrie; Jadi, Pramuji Handra; Setiawan, Tommy Avif (LPPM Universitas Pamulang, 2020)
This is a form of community service activity carried out by Polytechnic of State Finance STAN lecturers for students, lecturers, and other interested parties. The form of activities carried out is qualitative research training. This activity aims to provide education in making good qualitative research. The implementation of this activity was carried out through a web seminar because of the outbreak of Covid-19 which made it was impossible to carry out the activities face to face. The organizer of this activity is the Department of Accounting, Polytechnic of State Finance STAN. This activity was attended by students, lecturers and various other parties who came from all regions of Indonesia, from Aceh Province to Papua Province. The implementation of community service activities consists of several stages. The initial stage of the implementation of this activity is the planning stage through discussions in internal teams and between the team and the campus as the organizer to meet the expectations of participants and the organizer's target outcomes. The second stage is the implementation of activities in the form of delivery of material from one team member. The final stage is a follow-up on the implementation of the activity in the form of further discussion with participants who need additional explanations related to exposure. Based on participant's feedback delivered through the evaluation link, the results of community service activities indicate that the understanding of the participants has improved so that it can support the preparation of qualitative research projects.